Ganong's review of medical physiology - Barrett, Kim E.; Barman, Susan M. PhD; Brooks, Heddwen L. PhD; Yuan, Jason X.-J. MD, PhD (McGraw Hill Education, 2019)
For nearly half a century, Ganong's review of medical physiology has been helping those in medical field understand human and mammalian physiology. Applauded for its interesting and engaging written style, Ganong's concisely covers every important topic without sacrificing depth or readability and delivers more detailed, high-yield information per page than any other similar text or review. More than 550full-color illustrations combined with well-written, concise text make Ganong's the ideal USMLE review. This trusted resources can be used either as a companion to lectures and syllabi in discipline-based curricula, or a primary source in an integrated curriculum. Either way, there is no fiver review of the subject